Response of remote water vapor transport to large topographic effects and the multi-scale system during the “7.20” rainstorm event in Henan Province, China - Tang, Jiahui; Xu, Xiangde; Zhang, Shengjun; Xu, Hongxiong; Cai, Wenyue (Frontiers in Earth Science, 2023)
A high-resolution numerical simulation was carried out for the extremely heavy rainfall in Henan Province caused by the remote water vapor transport of the binary typhoons In-fa and Cempaka on July 20, 2021. The control simulation successfully captured the evolution process and spatial distribution of the rainfall. The key water vapor supply area of the event was a triangle moisture transport influence domain formed by the local low vortex and the multi-vapor vortex system at low latitude. By separating the effects of multiple tropical cyclones one by one, we found that In-fa dominated the main water vapor transport in the meridional direction, and directly affected the local water vapor supply in this rainfall process. Cempaka affected intermediate moisture transfer and impacted the location of precipitations, by regulating the distribution of water vapor input and output in the meridional and zonal directions. Removing Cempaka, In-fa, and binary typhoons can reduce the rainstorm area by about 7%, 65%, and 86%, respectively. These differences underscore the importance of binary typhoons in transforming a normal heavy rain event into a high-impact, record-breaking rain event. In addition, the Qinghai-Tibet Plateau exerts a modulation effect on the remote moisture transport of typhoons by multi-scale interactions. Eliminating the influence of plateau topography weakens the maximum precipitation by about 30% and the distribution of heavy rain by about 62%. After comprehensive diagnosis, a conceptual model of typhoon remote water vapor transport based on moisture multi-vortex structure under multi-scale interactions is proposed. The extreme and uncertain nature of this rainstorm event can be attributed to the maintenance and development of binary typhoons, the northward extension of the subtropical high, and the anomalous convergence mechanism of water vapor due to the large terrain blocking effect on the plateau.